A DOS METROS DE TI/FIVE FEET APART (2019) DE JUSTIN BALDONI: UNA HERRAMIENTA DE APRENDIZAJE SOBRE FIBROSIS QUÍSTICA. - BAILON-MOSCOSO, Natalia; CADME-MASSA, Fernando; FLORES-GUEVARA, Diana; GUALOTUÑA-CAMPOVERDE, Dagmar; NARANJO-QUEZADA, Andrea; TORRES-LOJÁN, Diana (Journal of Medicine & Movies / Revista de Medicina y Cine, 2022)
Movies are a helpful tool to learn and teach which allow us to depict from different points of view the complexity of the illness. In this paper we focus on the educational tools we saw in the movie Five feet apart about cystic fibrosis, where we can see the daily aspects that patients have to endure in a hospital, from their feeding, treatment and infections, as well as the importance of physical contact with the people around because they must keep a distance of 2 m between them. It also depicts the infections caused by multi-resistant bacteria like Burkholderia cepacia and the alternative methods to treat it like lung transplant which allows patients to extend their life expectancy.